1998
DOI: 10.1074/jbc.273.51.34623
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of a Cis-element and a Trans-acting Factor Involved in the Response to Polyamines and Polyamine Analogues in the Regulation of the Human Spermidine/Spermine N 1-Acetyltransferase Gene Transcription

Abstract: The superinduction of spermidine/spermine N 1 -acetyltransferase (SSAT) gene has been associated with a cytotoxic response to a new class of antineoplastic polyamine analogues. The initial mechanism of SSAT superinduction is an increase in transcription in response to analogue exposure. This increased transcription appears to be modulated through the association between a nuclear protein factor and a cis-element described here as the polyamine-responsive element (PRE). The PRE was identified as a 9-base pair s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 43 publications
2
77
1
Order By: Relevance
“…Thus, TNF␣ stimulation of SSAT may, in some cases, allow cells to reduce their growth rate when exposed to a stressful environment, and the observed cytotoxic drug responses may be an exaggerated extension of this normal response. Although more studies will be necessary to test this possibility, it is intriguing to consider the potential cross-talk that may occur between the polyamine response element (7,45), which is thought to mediate SSAT induction produced by cytotoxic polyamine analogues, and NFB and how such cross-talk might be exploited for therapeutic advantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TNF␣ stimulation of SSAT may, in some cases, allow cells to reduce their growth rate when exposed to a stressful environment, and the observed cytotoxic drug responses may be an exaggerated extension of this normal response. Although more studies will be necessary to test this possibility, it is intriguing to consider the potential cross-talk that may occur between the polyamine response element (7,45), which is thought to mediate SSAT induction produced by cytotoxic polyamine analogues, and NFB and how such cross-talk might be exploited for therapeutic advantage.…”
Section: Discussionmentioning
confidence: 99%
“…SSAT activity is highly regulated and is induced rapidly in response to a number of stimuli, including polyamines, polyamine analogues, hormones, physiological stimuli, drugs, and toxic agents (1). It has been shown that the regulation of SSAT by the natural polyamines and the anti-tumor polyamine analogues is through the polyamine response element (7). Further, the superinduction of SSAT by polyamine analogues has been implicated in the cell type-specific cytotoxic response of several important human tumors (8 -13).…”
mentioning
confidence: 99%
“…One of the mechanisms of PA-mediated effects on transcription leading to protein synthesis involves binding of trans-acting factors to PA-responsive, ciselement (PRE) identified in human Spd/Spm N 1 -acetyltransferase (SSAT) gene (Chen et al 1997;Wang et al 1998Wang et al , 2001). The sequence 5Ј-TATGACTAA-3Ј represents the PRE in human SSAT.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous SSAT activity is normally very low in cultured cells and tissues. Regulation of enzyme activity occurs via changes in the amount of enzyme protein, and these alterations are mediated through effects at several levels, including gene transcription, mRNA translation and protein turnover [3][4][5][6]. In the uninduced state, SSAT turns over very rapidly, although accurate measurements of the half-life are difficult to obtain because of the low level of the protein.…”
Section: Introductionmentioning
confidence: 99%